2002
DOI: 10.1007/s00428-002-0697-7
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the upper esophagus arising in heterotopic gastric mucosa: common pathogenesis with Barrett's adenocarcinoma?

Abstract: Adenocarcinoma of the upper esophagus arising in heterotopic gastric mucosa is a rare tumor, with only 15 cases reported to date. We report a case in a 61-year-old man complaining of dysphagia. The upper endoscopy revealed that the tumor measured 3 cm and was 22 cm distant from the incisivors. A hiatal hernia with erosive esophagitis of the distal esophagus was present. On microscopic examination the tumor corresponded to a poorly differentiated adenocarcinoma immunoreactive for cytokeratin (CK) 7 and p53. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 34 publications
(65 reference statements)
2
18
1
Order By: Relevance
“…The reported prevalence of intestinal metaplasia in EGMs is less than 20%, 16 and only 4 cases of intestinal metaplasia in an EGM with adenocarcinoma have been reported. 5,17,18 Therefore, the metaplasia-carcinoma sequence is not the major stream of carcinogenesis in adenocarcinoma arising from an EGM of the cervical esophagus. Furthermore, our patient had no gastroesophageal reflux disease endoscopically and symptomatically, and the relation of the carcinogenesis with gastroesophageal reflux disease was not clarified.…”
mentioning
confidence: 99%
“…The reported prevalence of intestinal metaplasia in EGMs is less than 20%, 16 and only 4 cases of intestinal metaplasia in an EGM with adenocarcinoma have been reported. 5,17,18 Therefore, the metaplasia-carcinoma sequence is not the major stream of carcinogenesis in adenocarcinoma arising from an EGM of the cervical esophagus. Furthermore, our patient had no gastroesophageal reflux disease endoscopically and symptomatically, and the relation of the carcinogenesis with gastroesophageal reflux disease was not clarified.…”
mentioning
confidence: 99%
“…The association between Barrett's esophagus and HGM has been suggested by many studies. Barrett's mucosa has been described in as many as 20 % of the patients having a HGM [3,8,10]. GERD has been shown as a common feature associated with both of these conditions [11].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these cases have been described in context with a heterotopic gastric mucosa (HGM) or Barrett's esophagus. The exact pathogenesis for the development of adenocarcinoma in cervical esophagus is not well understood and it has been suggested that adenocarcinoma developing in the HGM and Barrett's mucosa may share common etiopathogenesis [3]. A case of adenocarcinoma of cervical esophagus arising in the Barrett's mucosa is presented here.…”
Section: Introductionmentioning
confidence: 96%
“…The present case was classified as enteric cysts according to the classification of Kirwan et al (2) (4,5).…”
Section: Discussionmentioning
confidence: 99%